Efek Modernisasi Administrasi Perpajakannterhadap KepatuhannWajib Pajak - Giffary, Muhammad Rizky (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to determine the effect of modernization of tax administration on taxpayer compliance at KPP Pratama Bandung Tegallega. This study uses a survey approach with an explanatory method. The data collection technique in this study is primary data by distributing questionnaires to respondents with a total sample of 100 respondents. Sampling in this study using simple random sampling method. The data analysis technique used is Reality Test, Validity, Normality, Regression Coefficient, and Linear Regression 43.4% of taxpayer compliance is influenced by modernization of tax administration, while the rest is influenced by other factors. The hypothesis in this study shows that Ho is rejected and Ha is accepted. From the results of this study, tax modernization has a positive effect on taxpayer compliance.